Konsep Strict Liability dalam Hukum Acara Perdata Indonesia - Syahrul Machmud (Jurnal Media Justitia Nusantara, 2017)
This study aims to find out the concept of absolute liability in Indonesia's civil procedural legal system, especially regarding environmental disputes. Also examined the history of the development of strict liability in the common law legal system until it was adopted into Indonesia's civil procedural law. Theoretically this concept is still a concept found in several Indonesian laws. It's just how it is implemented in Indonesian judicial practice, until now there has been no further regulation. This study uses a type of normative juridical research, data collection is done through literature studies and document studies. The results of this study indicate that the concept of strict liability has been accepted in Indonesia's civil procedural law system, but at the implementation level there are no claims that use this strict liability concept.